(untitled) (AYUSHDHARA, 2021)
Dry eye syndrome (DES) is a common condition that causes pain and can lead to vision problems. Modern living has given rise to a massive increase in the incidence of vision threatening dry eye disease, around 10-30% of population living in industrialized countries suffer from dry eye syndrome (DES). According to Second International Dry Eye Workshop (DEWS II) in 2017 offered dry eye as it is a multifactorial ocular surface disorder defined by a loss of tear film homeostasis and ocular symptoms, in which tear film instability and hyperosmolarity, as well as ocular surface inflammation and injury, play a part in the etiology. If it is not controlled with in time it can lead to corneal blindness. Ayurveda proposes a comprehensive systemic & topical strategy in the treatment of dry eye syndrome, in contrast to the available modern medical treatment. In this publication, a case study of a Shushkakshipaka with many complications who was treated with dynamic Ayurvedic treatments & after continuous efforts patient got very significant results is being discussed here.